2022
DOI: 10.1007/s10488-022-01214-1
|View full text |Cite
|
Sign up to set email alerts
|

Family Involvement in PTSD Treatment: Perspectives from a Nationwide Sample of Veterans Health Administration Clinicians

Abstract: Social support is bidirectionally linked to symptoms of posttraumatic stress disorder (PTSD). Evidence suggests that family involvement in veterans’ mental health treatment is desired by both veterans and family members, and that such involvement has the potential to improve treatment outcomes. However, rates of family involvement are low in the Veterans Health Administration (VHA). We sought to understand VHA clinicians’ perspectives on family involvement in PTSD treatment by conducting qualitative interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…For example, providers discussed a positive attribute of FAMILIAR as the importance of aligning SP expectations of treatment with the reality of trauma-focused treatment, and several veterans/SP dyads reported that FAMILIAR helped the dyad to prepare for EBP sessions and know what to expect. These perspectives align with prior work showing that VA providers acknowledge that family involvement could enhance PTSD care, especially PE and CPT (Thompson-Hollands et al, 2022).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…For example, providers discussed a positive attribute of FAMILIAR as the importance of aligning SP expectations of treatment with the reality of trauma-focused treatment, and several veterans/SP dyads reported that FAMILIAR helped the dyad to prepare for EBP sessions and know what to expect. These perspectives align with prior work showing that VA providers acknowledge that family involvement could enhance PTSD care, especially PE and CPT (Thompson-Hollands et al, 2022).…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, implementing FAMILIAR and other family-involved interventions within VA and in other health systems will require system-level innovations in how to address reimbursement structures, documentation, flexible scheduling for employed SPs, and procedures to maintain veteran and SP confidentiality. Like prior studies, we identified concerns about limited staffing resources to offer family-involved interventions (Thompson-Hollands et al, 2022). Within mental health services, there may be a need to grow some providers’ skills in conjoint therapeutic approaches and knowledge of family-inclusive treatments (Thompson-Hollands et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…22 Furthermore, prior work suggests that veterans have a preference for including their family in treatment for PTSD [23][24][25] and VHA clinicians also have positive views regarding the importance of family-level treatment adjunctive to individual treatment for PTSD. 26 Recent VHA data on the utilization of family therapy in mental health clinics…”
Section: Discussionmentioning
confidence: 99%
“…As of 2020, about half of all military personnel were married, and about a third had at least 1 child, indicating a majority of veterans may have a close family member who could be included in treatment . Furthermore, prior work suggests that veterans have a preference for including their family in treatment for PTSD and VHA clinicians also have positive views regarding the importance of family-level treatment adjunctive to individual treatment for PTSD . Recent VHA data on the utilization of family therapy in mental health clinics shows that VHA patients diagnosed with PTSD report receiving more of any type of family therapy compared with those diagnosed with other mental health conditions .…”
Section: Discussionmentioning
confidence: 99%